Association of rs2073498 ala133ser gene polymorphism with risk towards lung cancer susceptibility in a north Indian population - Kaur, Harinder (My University, 2013)
The tumor suppressor gene RASSF1A (Ras association domain family 1 isoform A) regulates cell cycle regulation, apoptosis and microtubule stability and suffers from frequent allelic loss and gene silencing via promoter hypermethylation in a variety of human malignancies. An association between a single nucleotide polymorphism (SNP) at codon 133 of the RASSF1A gene, encoding either alanine (GCT) or serine (TCT), and human lung cancer risk in a North- Indian population was studied by investigating the distribution of the Ala133Ser SNP in 90 patients with lung cancer and 95 healthy controls by polymerase chain reaction and restriction enzyme-digestion assay. The individuals with Ser/Ser genotype showed increased risk of lung cancer, though data was statistically insignificant due to small size of population studied (OR: 2.03, 95% CI; 0.35-11.55, p value = 0.41). Risk of SQCC development was found to be significantly high in carriers of the Ser/Ser mutant alleles of Ala133Ser polymorphism when compared with homozygote Ala/Ala genotype (OR: 2.9, 95% CI; 1.25-6.80, p value=0.01).
Master of Science-Biotechnology
Keywords: RASSF1A; LUNG CANCER; POLYMORPHISM